FENOMENA LINGKUNGAN KERJA DAN PERSEPSI MAHASISWA TERHADAP PEMILIHAN KARIR SEBAGAI AUDITOR INTERNAL MAHASISWA JURUSAN AKUNTANSI STIE AMM MATARAM - Endang Kartini; Lalu Mimbar (Valid: Jurnal Ilmiah, 2017)
This study aims to: 1) analyze the influence of Work Environment and Student Perception on Career Selection As Internal Auditor For Students Accounting STIE AMM Mataram. 2) to analyze the Effect of Work Environment, and Student Perception Simultaneously (together) on Career Selection As Internal Auditor For Students Accounting Department STIE AMM Mataram. The results showed that the results of validity test correlation of each variable showed significant results, this means each variable is valid. The reliability test result shown in the Alpha value of all independent variables is reliable, since it has a value above Cronbach's Alpha Based on Standardized Items or larger 0.6 (α> 0.6). The result of regression analysis, the regression coefficient value of work environment variable and student perception as a whole is said to be significant because it has much greater value than (> 0,05). Testing simultaneously, there is a significant influence simultaneously (together) between Work environment, Student Perceptions of Career Selection As Internal Auditor of students majoring in accounting STIE AMM Mataram. The same thing happens, partially there is a significant influence between work environment variables, student perceptions of career selection as an internal auditor of students majoring in accounting STIE AMM Mataram